Al 'Adah Muhakkamah Rules and Their Applications Regarding the Contemporary Era Share Purchase and Sale Agreement - Akbar, Muhamad Iqbal; Bakri, Mohamad Fikri bin Mohd (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
The principles of